2019
DOI: 10.1177/0300060519870951
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Wernicke’s encephalopathy: a retrospective study of 17 cases

Abstract: ObjectiveNonalcoholic Wernicke’s encephalopathy (WE) is a devastating neuropsychiatric syndrome caused by thiamine deficiency. Although many case reports on WE have been published, more studies are required to guide the diagnosis and treatment of nonalcoholic WE.MethodsWe retrospectively studied patients who were diagnosed with WE in our hospital. Data on demographics, possible causes, phenomenology, and diagnostic and treatment delays were abstracted from medical records by chart reviews.ResultsSeventeen pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…Однако определение сывороточного магния не относится к рутинному биохимическому исследованию и не было выполнено в данном случае. Энцефалопатия Вернике у пациентов, не страдающих алкоголизмом, имеет в основном сложные клинические проявления и атипичное развитие заболевания [3,5,10,11]. Наш пациент в этом плане оказался исключением.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Однако определение сывороточного магния не относится к рутинному биохимическому исследованию и не было выполнено в данном случае. Энцефалопатия Вернике у пациентов, не страдающих алкоголизмом, имеет в основном сложные клинические проявления и атипичное развитие заболевания [3,5,10,11]. Наш пациент в этом плане оказался исключением.…”
Section: Discussionunclassified
“…Несмотря на указанную редкость патологии, только за последние несколько лет описано большое число клинических наблюдений энцефалопатии Вернике у пациентов, не злоупотребляющих алкоголем: при желудочно-кишечных расстройствах различного генеза (оперативные вмешательства, он ко ло ги че ские заболевания, беременность и др. ), голодании или строгих диетических ограничениях (строгое соблюдение поста), гипотрофии, нервной анорексии, травме головного мозга, энцефалите с поражением базальных ядер и височных долей, отравлении угарным газом [5][6][7][8][9][10][11][12][13]. Представляют интерес наблюдения энцефалопатии Верника у пациентов, перенесших трансплантацию печени, костного мозга, гемопоэтических стволовых клеток [14][15][16].…”
unclassified
“…Lesions can also be found atypically in the cerebellum, cranial nerve nucleus, red nucleus, caudate nucleus, cerebral cortex, and other atypical areas. Atypical findings are found more frequently in nonalcoholic patients[ 10 ]. Cerebellum involvement on imaging is rare, but autopsy studies have demonstrated that the anterior-superior vermis or anterior hemisphere is affected in more than half of patients with Wernicke’s encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…These include the medial thalami (85%), third ventricle (80%), periaqueductal gray matter (59%), mammillary bodies (45%), and the tectal plate (36%). Less commonly affected areas include the cranial nerve nuclei (18%), periventricular gray matter anterior to the fourth ventricle (7%), cerebellum (5%), vermis (4%), dentate nuclei (1.8%), and the precentral and postcentral cortices (1.8%) [ 1 , 2 , 5 , 23 ]. However, in both of our cases, the medial thalami were the only structures involved, thus adding to the diagnostic dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…Pulvinar/hockey stick signs have high specificity for vCJD [ 26 ] but can be seen in various other pathologies ( Table 3 ). Appropriate identification of these signs on MRI in combination with a patient’s clinical presentation is critical for appropriate diagnosis and treatment [ 23 ]. Patient A was diagnosed with vCJD because of the isolated pulvinar sign.…”
Section: Discussionmentioning
confidence: 99%